2015
DOI: 10.1016/j.redox.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Protein lipoxidation: Detection strategies and challenges

Abstract: Enzymatic and non-enzymatic lipid metabolism can give rise to reactive species that may covalently modify cellular or plasma proteins through a process known as lipoxidation. Under basal conditions, protein lipoxidation can contribute to normal cell homeostasis and participate in signaling or adaptive mechanisms, as exemplified by lipoxidation of Ras proteins or of the cytoskeletal protein vimentin, both of which behave as sensors of electrophilic species. Nevertheless, increased lipoxidation under pathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 114 publications
(164 reference statements)
3
82
0
Order By: Relevance
“…Aldehyde modification of vimentin on Cys 328 has previously been demonstrated in THP-1 cells treated with 4-HNE which when combined with our in vivo data validates its susceptibility to reactive species 68 . As important, regulation of vimentin on Cys 328 by reactive aldehydes has recently been described as a mechanism to regulate vimentin self-association and regulation of cellular organelles 69,70 .…”
Section: Discussionmentioning
confidence: 99%
“…Aldehyde modification of vimentin on Cys 328 has previously been demonstrated in THP-1 cells treated with 4-HNE which when combined with our in vivo data validates its susceptibility to reactive species 68 . As important, regulation of vimentin on Cys 328 by reactive aldehydes has recently been described as a mechanism to regulate vimentin self-association and regulation of cellular organelles 69,70 .…”
Section: Discussionmentioning
confidence: 99%
“…Several MS-based approaches to identify RCSs in free or adducted forms have been reported [33,34]. We have previously found that free plasma RCSs rapidly disappear (by almost 70% within 5 min) during reperfusion, since they form covalent adducts with plasma proteins [22].…”
Section: Discussionmentioning
confidence: 99%
“…In some of these studies, endogenous lipid electrophiles, typically generated under inflammatory conditions, have been used as models due to their broad reactivity towards nucleophiles and the availability of detection methods [13,42]. Also, coexistence of inflammatory conditions may potentiate the toxic effects of drugs or reduce the threshold at which they can induce adverse effects.…”
Section: Interactions With Inflammationmentioning
confidence: 99%
“…We have recently reviewed the methodology and challenges of proteomic analysis of modifications by various inflammatory mediators, which in many cases may be applicable to drug-protein interactions [42,44]. Nonetheless, combinations of approaches will be needed to fully characterize the protein modifications generated in pathophysiological conditions under therapeutic regimes.…”
Section: Interactions With Inflammationmentioning
confidence: 99%